الحجاج في كتاب المنهاج في ترتيب الحجاج لأبي الوليد الباجي - دراسة وصفية تحليلية - عيادي، منى, بحري، هناء (جامعة الوادي University Eloued, 2019)
حاولنا من خلال هذه الدراسة معرفة حيثيات الحجاج عند أبي الوليد الباجي ، درسنا لغة المنهاج الأصولية دراسة تحمل أبعادا حجاجية، فتبين أن لغة الباجي تمتاز بالسمة الحجاجية. وتوصلنا إلى توصيف ملامح النظرية الحجاجية الخاصة بالباجي من خلال اخضاعها لشروط النظرية اللغوية التي توصلنا بها إلى المفاهيم الأساسية التي قام عليها المنهاج وهي "التشابه والوظيفة والحكم"،ومنه فالحجاج عنده ينطلق من مقدمات علمية استدلالية وصولا إلى المفاهيم التي تفضي إلى أحكام. We tried through this study to know the reasons of the pilgrims at Abi Al-Walid Al-Baji, we studied the language of the curriculum fundamentalist study carrying the dimensions of the pilgrims, it turns out that the language of Baji characteristic of the pilgrims. We came to describe the characteristics of the Pilgrim theory of Baji by subjecting them to the terms of the linguistic theory which we have reached to the basic concepts on which the curriculum is based on "similarity, function and governance." Hence, the Hajj has its starting point from scientific evidence to the concepts that lead to judgments
Keywords: الحجاج- الجدل- الاستدلال- المناظرة- المطالبة- الاعتراض- المعارضة.; argument - Controversy - Inference - Opposition - Claim - Opposition - Opposition.